Sustainable Supplier Selection Using AHP: A Green Purchasing Approach at PT Dapensi Trio Usaha - Prastyantoro, Riharsono; Purnomo, Agus; Gunawan, Andri (Dinasti Publisher, 2024)
Green purchasing is an important issue in the manufacturing world, where all lines must implement the green concept in order to achieve a green concept that is friendly to the environment. PT Dapensi Trio Usaha in meeting the needs of its customers is faced with problems related to the selection of supplier criteria that have a green category so that it is hoped that later the procurement of goods that containing chemicals can meet the green standards set by ISO 14001. In the procurement process of goods containing chemicals, there are several vendors who have passed the administrative selection and can proceed directly to the tender stage. Among the companies that have met the administrative requirements are PT